Use of a fictitious community-based virtual teaching platform to aid in the teaching of pharmacy practice skills: Student perspectives after initial implementation - Curley, Louise E. (J Pharm Policy Pract, 2016)
BACKGROUND: Providing patient-centred care requires pharmacy students to learn how to interact effectively and understand individual differences that can influence patients’ health. The School of Pharmacy at The University of Auckland, New Zealand (NZ), developed a virtual teaching platform, called NZ Pharmville, which consisted of twenty-one community-based patients who are members of six families; each family had a video vignette associated with it. Bachelor of Pharmacy (BPharm) students, enrolled in the third year pharmacy practice course, were able to view these recorded vignettes as part of their weekly pre-laboratory work for the course. All the clinical cases within the course were based on this community, with the aim of increasing the realism in the practical sessions and increasing patient-centred learning. This study aimed to explore the perspectives of pharmacy students regarding the integration of this virtual community into a third year undergraduate pharmacy practice course. METHODS: An anonymous, voluntary survey which consisted of twenty-one items, 13 requiring a Likert scale response and 8 requiring free text responses, was distributed to all students who had completed the third year pharmacy practice course. The responses to the questions were collated and analysed. Responses to questions one to thirteen were recorded in Excel, and results were presented as the combination of strongly agree and agree, strongly disagree and disagree and neutral. Responses to free text questions were read multiple times before being coded by two members of the research team into broad themes aligned to the overall aims of the evaluation. RESULTS: Eighty-six (80.4 %) of the eligible students completed the survey and the majority of responses were positive towards the benefits of using the virtual community in the course. Responses indicated that many of the students found the integration of the virtual community to be useful preparation for their practical sessions and the majority of students felt that the vignettes made it easier to develop empathy for the patients rather than reading about them. CONCLUSION: The use of virtual communities, for example, NZ Pharmville, show promise as a platform to aid in teaching and learning. The resources in NZ Pharmville allow students ongoing access to patient video clips that attempt to depict a real life situation, and enable students to engage with the fictional characters. The virtual community provided an educational experience which was well received by students. This teaching method appeared to promote active patient-centered learning and allowed students to reflect on and revisit these skills on a weekly basis.